The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1160/th17-01-0065
|View full text |Cite
|
Sign up to set email alerts
|

NOACs for treatment of venous thromboembolism in clinical practice

Abstract: SummaryRandomised controlled trials have provided important information on the efficacy and safety of the non-vitamin K antagonist oral anticoagulants (NOACs) for treatment of venous thromboembolism (VTE), leading to registration and increasing use in clinical practice. Many questions remain to be answered, and observational studies are often more suitable for answering "real-world" questions than randomised controlled trials. Patient satisfaction, quality of life, and adherence and persistence in clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In an analysis of Optum data, reduced dose rivaroxaban was associated with (nonsignificant) stroke risk compared to warfarin. [50] Interestingly, and similar to our analysis, that pattern was not seen for dabigatran or apixaban. There is a growing body of literature suggesting that inappropriate DOAC dosing is commonplace.…”
Section: Discussionsupporting
confidence: 88%
“…In an analysis of Optum data, reduced dose rivaroxaban was associated with (nonsignificant) stroke risk compared to warfarin. [50] Interestingly, and similar to our analysis, that pattern was not seen for dabigatran or apixaban. There is a growing body of literature suggesting that inappropriate DOAC dosing is commonplace.…”
Section: Discussionsupporting
confidence: 88%
“…49,57 Moreover, optimal adherence is essential to ensure both efficacy and safety with anticoagulant therapy and adherence to OACs remains a challenge in clinical practice. 3,5,13 A recent study that assessed 12-month adherence and persistence with OACs reported adherence rates of 63.1 to 66.5% with NOACs, compared with 55.2% with VKAs, and persistence with NOACs of 61.4 to 78.7%, compared with 65.9% with VKAs. 4 Moreover, it demonstrated heterogeneity among different NOACs, possibility due to different regimens.…”
Section: Discussionmentioning
confidence: 99%
“…DOACs are now widely used in clinical practice, 18 19 and are included—together with warfarin—as the standard of care for VTE treatment in current guidelines. 7 Given the options of warfarin versus DOACs, when making decisions providers and patients take into consideration factors such as cost, priorities about specific adverse outcomes, convenience and patient preference.…”
Section: Introductionmentioning
confidence: 99%